The Monkey Study, Mandatory Military Retirement, and Legitimate Humanitarian Assistance / Disaster Relief (HA/DR) / Public Health Post-Service Paramilitary Substitutes: Letter to the Editor - Ralph J Johnson (Journal of Human Health Research, 2024)
A letter to the editor comments on animal research ethics, post‑service roles in humanitarian response, and public health preparedness. It advocates clear oversight, training, and accountability frameworks for paramilitary substitutes in HA/DR.
Keywords: Mandatory Military Retirement